The assessment of finger photoplethysmography fitness index (PPGF) among young men with cardiovascular disease risk factors: a cross sectional study - Amilia Aminuddin,; Zaiton Zakaria,; Kalaivani Chellappan,; Azizah Ugusman,; Norizam S,; Nor Anita MMN, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Two new vascular health markers which are derived from finger photoplethysmography (PPG) waveform have been introduced based on Malaysian population, namely PPG fitness index (PPGF) and vascular risk prediction index (VRPI). The objectives of this study were to investigate the associations between PPGF and other cardiovascular disease (CVD) markers such as carotid femoral pulse wave velocity (PWVCF), to compare PPGF between those with and without CVD risk factors and to determine the sensitivity of VRPI in identifying young subjects with CVD risk factors. A total of 114 men age 20 to 40 yrs with and without CVD risk factors were recruited. Risk factors included hypertension, smoking, dyslipidemia, abdominal obesity and family history of premature CVD. Subjects were divided into healthy, those with one risk factor and those with at least two risk factors. Their weight, height, peripheral and central blood pressure (BP), PWVCF and PPGF were measured and the sensitivity of VRPI in predicting subjects with CVD risk factor was calculated. Data was analyzed via SPSS version 15 and p < 0.05 was considered significant. The mean age of the subjects was 28.94 ± 4.86 yrs. No differences in PPGF was observed between groups (p > 0.05). The independent variables for PPGF were forward pressure (Beta = 0.35, p < 0.01), PWVCF (Beta = -0.26, p < 0.01), systolic BP (Beta = -0.26, p = 0.04) and height (Beta = 0.24, p < 0.01). The sensitivity of VRPI was 82.02%. In conclusion, PPGF was correlated to PWVCF and may be a potential marker of arterial stiffness. In addition, VRPI is sensitive to be used as an early screening of CVD risk factors.